Socio Demographic Factors affecting the Oral Health Status and Behaviour of Pregnant Women: A South Indian Context - R S, Dhanya; Pushpanjali, K (Bangladesh Journal of Medical Science, 2023)
Aim: To assess Social and demographic factors affecting the oral health status and behaviour of pregnant women in Kerala. Methodology: The present cross-sectional study was conducted in a group of expecting mothers at 2 private hospitals in Trichur district, Kerala, India. A questionnaire was used to assess the social and demographic factors affecting the oral health status and behaviour of pregnant women. Results: Study subjects having a professional education status did not having any periodontal pocket (CPI score 3 and 4). 85.7 % of the Study subjects having professional education status brushed twice daily whereas only 7.7 % of the study subjects having intermediate education or diploma brushed twice daily. There was a statistically significant difference between BPL status and frequency of brushing, as well as financial independence and number of teeth missing. CPI & LOA score was associated with sociodemographic factors. Conclusion: Social factors like SES etc act as a strong hindrance which lead to less use of dental health care services. Dental health education has to be given to overcome this. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.25-32